A Case of Infectious Keratitis Associated with Rigid Gas Permeable Contact Lens Use in a Keratoconus Patient - Hajirah Salam; Rinda Wati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Keratoconus is a non-inflammatory corneal ectatic disorder characterized by progressive corneal thinning and ectasia, leading to irregular astigmatism and visual impairment. Rigid gas permeable (RGP) contact lenses are often prescribed to manage keratoconus; however, improper use can lead to complications such as infectious keratitis. Case presentation: We present a case of a 25-year-old female with keratoconus who developed infectious keratitis after three months of RGP lens wear. The patient presented with ocular discomfort, pain, photophobia, and redness in the left eye. Clinical examination revealed conjunctival and ciliary injection, a paracentral corneal infiltrate, and decreased visual acuity. Corneal pachymetry confirmed bilateral corneal thinning. The patient was diagnosed with bilateral keratoconus, bilateral compound myopic astigmatism, and left-eye infectious keratitis. Treatment included discontinuation of RGP lens wear, topical antibiotic therapy, and artificial tears. After two weeks of treatment, the corneal infiltrate resolved, and the patient was allowed to resume RGP lens wear with strict adherence to hygiene protocols. Conclusion: This case underscores the importance of patient education and meticulous lens hygiene in preventing infectious keratitis and other complications associated with RGP lens wear in keratoconus patients. Regular follow-up examinations are crucial to monitor for signs of complications and ensure optimal lens fit. By adhering to these guidelines, clinicians can help to ensure the safe and effective use of RGP lenses in keratoconus patients.